Études Mésopotamiennes = Mésopotamian studies. - Marti, Lionel,; Rouault, Olivier,; Tenu, Aline, (Archaeopress Archaeology, 2023)
This volume is in two parts. The first part corresponds to the proceedings of a colloquium organised by Maria Grazia Masetti-Rouault. It explores the crisis of the State and the Monarchy between the 13th and 10th centuries in Northern Mesopotamia and Syria from archaeological, textual and iconographic sources. The second part is dedicated to archaeological and textual studies from three archaeological sites that are currently being excavated in Iraqi Kurdistan - Qasr Shemamoq, Kilik Mishik and Kunara.